MENGATASI HAMBATAN PEMELIHARAAN ITIK SECARA EKSTENSIP (DIGEMBALAKAN) - N.N, SURYANI.; BUDAARSA, K.; CANDRAWATI, D. P.M. A.; MARIANI, N. P. (Buletin Udayana Mengabdi, 2012)
ABSTRACT The public service activity at Banjar Cengkok, Baha village, Mengwi district, Badung regency has been held on August 25 th 2007. This activity was aimed to surmount all barriers in raising ducks extensively (by herding), specifically in terms of low egg production and in high bereft of them. The target of this activity was Kembang Sari duck breeder group which consists of 10 breeders. The methods that has been used were extension in connection with nutrition needs of ducks and to give information regarding the additional food that can be given to increase their productivity. Besides extension and discussion, another support as nylon net and rope have also been given to the breeders in order to help to create more security when the ducks are in herding.